Easily Missed: A Case Series of New Heart Failure in Young Adults - Eric J. Hall; Jonathan Menachem; Lynne Warner Stevenson; Jessica Huston (Case Reports in Medicine)
Background. While uncommon, heart failure (HF) can present in young adults from a variety of causes. Identifying HF in a young patient presents many challenges, the foremost of which is recognition of the signs and symptoms of HF. Case Summary. We present four cases of new diagnosis of HF (due to familial cardiomyopathy, tachycardia-induced cardiomyopathy, spontaneous coronary artery dissection, and peripartum cardiomyopathy) to highlight the range of etiologies and presentations requiring recognition in this patient population. Discussion. A high index of suspicion is needed to diagnose HF in young adults, who may not present with classic signs and symptoms. Young adults represent a unique patient population that differs from the older patients with HF. Young adults with newly diagnosed HF should be promptly referred to a center offering full diagnostic capabilities and advanced cardiac therapies.